Planejamento evasivo para o manejo da ferrugem do eucalipto (Puccinia psidii) - Silva, Lilianne Gomes da, (2013)
The Eucalyptus plantation represents the main alternative for the forestry production in the state of Espírito Santo. Wood is mainly for pulp and paper production, and also used as raw material for construction, furniture production, firewood and charcoal